Population Pharmacokinetics of Everolimus in Relation to Clinical Outcomes in Patients With Advanced Renal Cell Carcinoma. Issue 6 (December 2016) - Tanaka, Atsuko; Yano, Ikuko; Shinsako, Keiko; Sato, Eriko; Fukudo, Masahide; Masuda, Satohiro; Yamasaki, Toshinari; Kamba, Tomomi; Ogawa, Osamu; Matsubara, Kazuo
Abstract : Background: Everolimus has been used for the treatment of unresectable or metastatic renal cell carcinoma (RCC). Here, we measured blood concentrations of everolimus to obtain the population pharmacokinetic parameters and to examine the relationship between blood concentration and clinical outcomes. Methods: Twenty-two Japanese patients were enrolled. Blood samples were collected before and 2, 4, 8, and 24 hours after drug administration on days 1 and 8 of everolimus therapy (5 or 10 mg) from inpatients; occasional samples were collected from outpatients. Blood concentrations of everolimus were measured by high-performance liquid chromatography with tandem mass spectrometry. Population pharmacokinetic analysis was conducted using the NONMEM software. Results: Everolimus pharmacokinetics was best described by a 2-compartment model with population mean estimates of apparent oral clearance of 10.0 L/h and an interindividual variability of 42.4%. There was no relationship between overall best responses and the predicted trough concentrations at day 8. The predicted trough concentration in patients who terminated everolimus treatment owing to adverse drug reactions (ADRs) was significantly higher than in patients who stopped the treatment owing to disease progression or other reasons (27.6 ± 3.1 versus 15.7 ± 2.3 ng/mL; mean ± SEM). Patients who terminated the treatment owing to ADRs had significantly shorter time-to-treatment failure than other patients (112 versus 187 days, median). Conclusions: This study reports the first population pharmacokinetic parameters of everolimus in patients with RCC. Individual dose adjustment based on everolimus blood concentrations helps to avoid early drug cessation due to ADRs.